Seismic behaviour of cracked concrete gravity dams. - Pekau, O. A. (Earthquake engineering & structural dynamics.)
A finite element model of incremental displacement constraint equations (IDCE), based on an existing node-to-surface concept, is implemented to deal with dynamic contact surfaces in the seismic behaviour analysis of cracked concrete gravity dams. After verification for sliding, rocking and impact, the IDCE model is applied to study the seismic responses of concrete gravity dams with different profiles and crack locations for a variety of parameters, such as coefficient of friction, water level and type of earthquake, as well as impact damping based on the concept of coefficient of restitution. It is revealed that cracked concrete gravity dams can experience not only sliding and rocking modes, but also the drifting mode in some cases of crack either at the base or at a height. Downstream sliding is normally accompanied by rocking, especially for the cases of crack at a height. Due to rocking and drifting, a cracked dam may still acquire a certain amount of residual sliding even if the effective coefficient of friction is relatively high.